2020
DOI: 10.1007/s00125-020-05159-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional profiling of human islets: from heterogeneity to human phenotypes

Abstract: Efforts to phenotype pancreatic islets have contributed tremendously to our present understanding of endocrine function and diabetes. A continued evolution in approaches to study islet physiology is important given the need to establish reference points for mature islet functionality, understanding biological variation amongst individuals and cells, and the ongoing appreciation of the role for islets in diabetes susceptibility. Recent efforts in islet biology have focused on technological improvements in imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…This finding is important regarding studies on heterogeneity and functional specialization within the islet beta cell [ 87 , 88 ]. More specifically, it has been suggested that beta cells differ at many different organizational levels, from the expression of specific genes to their functional maturity in terms of signal synchronization and insulin secretion [ 5 , 10 , 87 , 89 95 ]. Under NMDAR inhibition, the functional connectivity increased irrespective of a cell´s role as a very well-connected or less well-connected cell, which suggests that MK-801 exerts its effect rather homogeneously across the beta cell population, or the enhancement of intercellular signal propagation in cells more susceptible to the drug is enough to bring about a global increase in functional connectivity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding is important regarding studies on heterogeneity and functional specialization within the islet beta cell [ 87 , 88 ]. More specifically, it has been suggested that beta cells differ at many different organizational levels, from the expression of specific genes to their functional maturity in terms of signal synchronization and insulin secretion [ 5 , 10 , 87 , 89 95 ]. Under NMDAR inhibition, the functional connectivity increased irrespective of a cell´s role as a very well-connected or less well-connected cell, which suggests that MK-801 exerts its effect rather homogeneously across the beta cell population, or the enhancement of intercellular signal propagation in cells more susceptible to the drug is enough to bring about a global increase in functional connectivity.…”
Section: Discussionmentioning
confidence: 98%
“…Both well-connected cells and cells with fewer connections displayed approximately the same relative increase in node degrees (see S3 Fig). This finding is important regarding studies on heterogeneity and functional specialization within the islet beta cell [87,88]. More specifically, it has been suggested that beta cells differ at many different organizational levels, from the expression of specific genes to their functional maturity in terms of signal synchronization and insulin secretion [5,10,87,[89][90][91][92][93][94][95].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we recorded b cell activation, activity during the plateau phase, and deactivation following stimulation with both physiological and supraphysiological glucose concentrations, extracted, and analyzed both classical and network functional parameters, and explored the relations between them. The latter is crucial for a deeper understanding of various aspects of recently reported heterogeneity within islets (1,41,(100)(101)(102)(103)(104)(105).…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 , 38 In recent years, much attention has been given to islet cell heterogeneity, and that subtypes of β-cells and α-cells have different gene expression and physiological roles. 42 , 43 Expression studies are snapshots, and it has not yet been described if a cell stays within a certain expression pattern forever. A recent study describes the likelihood of dynamic changes in expression over time and how β-cells take turns to have different set-ups, just as migrating birds with a leader that changes.…”
Section: Evidence For Endocrine Pancreatic Dysfunction Leading To Cfrdmentioning
confidence: 99%